KELUARGA BERENCANA DITINJAU DARI HUKUM ISLAM - Azura Aprilla; Sekar Putri Enjela; Muhammad Wahyudi (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2021)
The Indonesia and Demographic Health Survey (IDHS) in 2017 reported a gap between urban and rural contraceptive use in Gorontalo Province, Indonesia. This urban-rural inequality calls for an exploration of its drivers. Hence, this study aims at reviewing the literature to analyze the level of use of contraception for married women in rural and urban areas by examining several factors, such as education, knowledge, age, occupation, information provision, and source of service.The results shows that despite a higher knowledge of contraception in urban married women than their rural counterpart, modern contraceptive use is higher in mral areas than in urban areas. Moreover, provision of information plays a larger role in contraceptive use compared to other aspects. Furthermore, the low contraceptive use among urban women is due to the limited services, where there is a mismatch between the needs and the availability of contraception.